Gravacin as an inhibitor of the auxin transport-activating protein kinase D6PK in Arabidopsis - Chen, Meng; Yang, Zhisen; Peng, Yakun; Sun, Lianghanxiao; Liu, Xin; Sun, Linfeng; Tan, Shutang (Frontiers in Plant Science, 2025)
The phytohormone auxin plays a central role in plant growth and development. D6PK, a member of the AGC kinase family, phosphorylates PIN-FORMED (PIN) auxin transporters, thereby regulating PIN activity and polar auxin transport. In this study, we demonstrated that gravacin, a synthetic compound, functions as an inhibitor that targets D6PK in plants. Physiological and cell biology experiments revealed that the phenotypes of gravacin-treated plants were similar to those of d6pk d6pkl1 d6pkl2 (d0 d1 d2) triple mutants. Furthermore, in vitro kinase assays confirmed that gravacin directly inhibited the kinase activity of D6PK. Thus, by combining phenotypic analysis with cell biological and biochemical experiments, this research revealed that gravacin is an inhibitor of D6PK and elucidated the underlying mechanism. Our work provides a chemical tool that can be used to further dissect the role of D6PK and related physiological processes.